Biologically active substances of elder: Properties, methods of extraction and preservation - L. Ch. Burak; A. N. Sapach (Пищевые системы, 2023)
Anthocyanins and polyphenols are the main biologically active substances in elderberry. Extraction methods exert a significant effect on the extraction effectiveness, bioavailability and preservation of biologically active compounds. The aim of this work was a review of the published results of scientific studies of elderberry and products of its processing, their effect on the body, as well as examination of methods for extraction and encapsulation of biologically active substances of elderberry. The review includes papers in English and Russian. A search for foreign literature in English on this theme was carried out in the bibliographic databases Google Scholar, Scopus, Web of Science, Elsevier, ResearchGate. To select scientific papers in Russian, a search was done in the scientific electronic library eLIBRARY.RU by keywords. The review of the scientific publications shows that the results of numerous studies confirm the high antioxidant activity of elderberry (Sambucus nigra L.), as well as wild elderberry (Sambucus ebulus), growing on the territory of the Belarus Republic and in other countries of Europe, Asia, North Africa and North America. This plant is applied in the traditional medicine and is used in the food industry as raw materials for creation of prophylactic and functional products due to the presence in the chemical composition of elderberry (Sambucus nigra L.) of bioactive flavonoids such as quercetin, kempherol and rutin, and other phenolic compounds. Bioactive compounds of elderberry possess several unique biological and pharmacological properties including the antioxidant, anti-tumor, anti-depressive, anti-diabetic, antiviral and antibacterial activities. To extract bioactive substances from elderberry, traditional extraction methods are used, such as maceration and Soxhlet extraction, as well as modern promising “green” technologies (for example, supercritical fluids, pulsed electric field, emulsion liquid extraction, microwave-assisted and ultrasound-assisted extraction). To preserve and protect biologically active substances in elderberry, encapsulation methods that are most effective are employed. The materials of this paper can be used in future studies on optimization of extraction processes to increase the nutritional value and antioxidant activity of new functional foods, food additives and products of pharmaceutical industry.